Contribution to the sustainable management of water and soil resources in North-West Benin: characterization of the watershed heads of the Ouémé and Pendjari rivers in the commune of Copargo - Kamarou Faré Kondo; Ibrahim Tchakala; Masamaéya Dadja-Toyou Gnazou; Wèré Gédéon Sambienou; Firmin Adandedji; Ousmane Boukari; Daouda Mama (European Scientific Journal, ESJ, 2024)
Watershed heads, which are the upstream areas where rivers originate, are crucial zones for water resource management. Defined by first- and second-order streams according to Strahler’s classification, watershed heads are often overlooked in water resource planning due to limited information and knowledge about these areas. This oversight leads to anthropogenic pressures and negative impacts on water quality, soils, and biodiversity. The objective of the present study is to characterize the watershed heads of the Ouémé and Pendjari rivers within the Copargo municipality, with the aim of improving understanding of sustainable water and soil resource management in this region. For this purpose, mapping techniques and geographic information systems were employed to identify and delineate the watershed heads. Criteria related to morphometry, land use, and land cover were utilized to characterize the areas of the watershed heads. Exploratory and principal component analyses based on various characteristics of the watershed heads were conducted using the R software, which highlighted the different challenges associated with these areas. The study delineated 25 watershed heads: 14 in the Pendjari watershed and 11 in the Ouémé watershed, revealing their surface area and occupancy within the respective watersheds. The average unit area of the watershed heads is 23.6 km² in the Ouémé watershed and 21 km² in the Pendjari watershed. Across all watershed heads, the Gravelius compactness index ranges from 1.2 to 1.5, while slopes vary from 1.5% to 4.5%. Most watershed heads in Copargo are characterized by high proportions of agricultural land, moderate forest cover, and low levels of urbanized area. The high proportion of agricultural land has significant implications for water and soil resources. The results of this study provide valuable data for decision-makers and reveal the vulnerability of watershed heads to anthropogenic pressures. With a view to assessing the impact of anthropogenic pressure on the water resources of the study area, it would be beneficial in the future to proceed with the physicochemical and bacteriological characterization of these resources.